Language ideologies and media representation: framing Madurese dialects in Indonesian television news - Fadilah Wasiqah (Indonesian Journal of Language and Communication Studies, 2026)
Background: Indonesian television news operates within a sociolinguistic landscape where standard language ideology often shapes the representation of regional dialects, influencing public perceptions and linguistic equity. Objective: This study aims to examine how language ideologies, framing strategies, and multimodal practices interact to construct the portrayal of the Madurese dialect in provincial news broadcasts. Method: Using a qualitative design, the research integrates Critical Discourse Analysis, Framing Analysis, and Multimodal Discourse Analysis on purposively sampled TVRI Jatim segments containing dialectal speech, captions, and narration. Results: The results show that standard language ideology dominates, with dialects frequently reframed into standardized Indonesian, symbolically linked to rural identity, and commodified as cultural elements. Framing patterns often position dialect use within problem-oriented narratives, attributing socio-economic challenges to linguistic proficiency while offering assimilationist solutions. Multimodal analysis reveals visual and compositional choices that reinforce linguistic hierarchies, with captions simplifying dialectal content and visuals emphasizing traditional settings. Implication: These findings imply that broadcast media must adopt editorial practices that balance communicative clarity with equitable representation, fostering more inclusive and accurate portrayals of linguistic diversity. Novelty: This study contributes to the integration of critical, framing, and multimodal discourse approaches to reveal how standard language ideology systematically mediates and reshapes the representation of regional dialects in Indonesian television news.